2010
DOI: 10.1039/c000353k
|View full text |Cite
|
Sign up to set email alerts
|

Natural abundance high field 43Ca solid state NMR in cement science

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
5
23
0
Order By: Relevance
“…It is immediately clear that the observed 35/37 Cl SSNMR line shapes and EFG tensor parameters are inconsistent with the prior literature account for CaCl 2 . 46 The presently measured C Q ( 35 Cl) value of 8.82 (8) MHz is more than twice as large as the values observed for other anhydrous and hydrated group 2 metal chlorides. 44,46,69 This is primarily attributed to the arrangement of the Ca 2+ ions within the first coordination sphere of each chloride, which forms a distorted trigonal plane.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is immediately clear that the observed 35/37 Cl SSNMR line shapes and EFG tensor parameters are inconsistent with the prior literature account for CaCl 2 . 46 The presently measured C Q ( 35 Cl) value of 8.82 (8) MHz is more than twice as large as the values observed for other anhydrous and hydrated group 2 metal chlorides. 44,46,69 This is primarily attributed to the arrangement of the Ca 2+ ions within the first coordination sphere of each chloride, which forms a distorted trigonal plane.…”
Section: Resultsmentioning
confidence: 83%
“…[4][5][6] These tensors are important SSNMR observables, and a number of recent studies have illustrated that magnetic shielding and EFG tensor calculations using GIPAW DFT can provide additional insights in the study of a variety of chemical systems. [7][8][9][10][11][12][13][14][15][16][17] There is an increasing interest in "NMR crystallography", which pertains to obtaining molecular-level and crystal structure information for solid materials using SSNMR data. 18 Although there have been a number of exciting recent advances in this area of research, 6,[19][20][21][22][23][24][25] one cannot currently convert SSNMR data into a unique solid-state structure in a completely generalized manner.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Moudrakovski et al 39 using 43 Ca NMR showed that there is little change in the signal from Ca compared to tobermorite for C-S-Hs with C/S ratios of up to 1.5. While we find no significant change in the average Ca-O distance with C/S ratio in our X-ray PDFs, Gaussian fits to the peak reveal a systematic decrease in the average Ca coordination number.…”
Section: Resultsmentioning
confidence: 98%
“…Studies by Moudrakovski et al . using 43 Ca NMR showed that there is little change in the signal from Ca compared to tobermorite for C–S–Hs with C/S ratios of up to 1.5.…”
Section: Resultsmentioning
confidence: 99%
“…1a), the 43 Ca EFG tensor must possess axial symmetry (i.e., the asymmetry parameter of the EFG tensor, Z Q , must equal 0), 75 which is interestingly in contrast with several earlier 43 Ca NMR measurements that report a small, albeit consistently nonzero Z Q ( 43 Ca) value. 33,35,76,77 Oxygen-17 SSNMR results have also been presented, 78,79 and while several measurements of the 43 Ca EFG tensor in Ca(OH) 2 have been conducted, we are not aware of any attempts to completely determine the calcium CSA tensor in this material, which also includes the measurement of the Euler angles relating the CSA and EFG tensor PASs.…”
Section: A Calcium Hydroxide Ca(oh)mentioning
confidence: 99%